2011
DOI: 10.1111/j.1440-1797.2011.01525.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological predictors for renal prognosis in diabetic nephropathy in diabetes mellitus type 2 patients with overt proteinuria

Abstract: Interstitial lesions but not glomerular lesions were a significant predictor for renal prognosis in diabetic nephropathy in type 2 diabetes patients with overt proteinuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
4
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 29 publications
7
75
4
3
Order By: Relevance
“…not only a glomerular lesion, but also IFTA and interstitial inflammation had a strong impact on the renal prognosis [7] . Several other reports have also suggested the importance of these pathological lesions in assessing the renal outcome [8,10,16] . Nevertheless, because the correlation between organ changes in the kidney is so complex [7] , the net effect of kidney damage on renal prognosis remained unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…not only a glomerular lesion, but also IFTA and interstitial inflammation had a strong impact on the renal prognosis [7] . Several other reports have also suggested the importance of these pathological lesions in assessing the renal outcome [8,10,16] . Nevertheless, because the correlation between organ changes in the kidney is so complex [7] , the net effect of kidney damage on renal prognosis remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Several large studies showed that a high urinary albumin-to-creatinine ratio and a low estimated glomerular filtration rate (eGFR) are predictors for diabetic ESRD and death [2][3][4][5] . In addition to these clinical parameters, after the development of pathological classification of DN by Tervaert et al [6] , several studies suggested that both glomerular and interstitial damage are independently associated with ESRD [7][8][9][10] . But it remained unknown how much the separate sorts of damage revealed by renal biopsy -with varying degrees of severity for each patientimpact the overall renal outcome.…”
Section: A Pathological Scoring System To Predict Renal Outcome In DImentioning
confidence: 99%
“…The area of TI fibrosis was slightly lower (16.8%) in the 2K-obese ZSF-1 group compared to the 1K-obese rats at the 24-week point of the study. A relationship between the development of TI fibrosis and a decline in GFR and/or patient survival has been controversial with studies presenting evidence on either side of this putative linkage [24,25,26,27], but a recent large scale study with DN patients demonstrated a strong link between interstitial fibrosis and renal outcome independent of other clinical features [28]. In the same study, glomerular lesions were also associated with renal outcome and correlated with the development of interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that changes in the tubulointerstitial tissue compartment are a prominent feature of the pathophysiologic processes that lead to progression of kidney disease. First, the clinical kidney outcome of ESRD, for which dialysis or a renal transplantation is needed, is predicted by the severity of glomerular lesions but more strongly predicted by the severity of tubulointerstitial damage (tubular atrophy, interstitial inflammation, and interstitial fibrosis) (9). Second, numerous in vitro and in vivo studies have reported that increased glomerular albumin leakage stimulates proinflammatory and profibrotic signals that directly contribute to tubulointerstitial damage.…”
Section: Albumin Leakage Causes Renal Damagementioning
confidence: 99%